2006
DOI: 10.1007/s10591-006-9019-6
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Marital Satisfaction among Graduate Students: an Analysis of the Perceptions of Masters and Doctoral-Students

Abstract: This study investigated marital satisfaction among graduate students. Using the Marital Satisfaction Inventory-R (MSI-R), 65 graduate students were surveyed. The results revealed multiple common areas of marital concern based on degree program of the student. These findings offer implications for psychoeducational and responsive interventions for clinicians working with this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…These themes were the following: (a) relationships with family, faculty and peers; (b) determination, organization skills, and time management; (c) program flexibility and course relevance; (d) career advancement and financial reward; and (e) clear doctoral program expectations. These themes are consistent with previous research suggesting persistence and attrition in doctoral programs are associated with personal needs and institutional factors (Golde, 2006;Lovitts, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These themes were the following: (a) relationships with family, faculty and peers; (b) determination, organization skills, and time management; (c) program flexibility and course relevance; (d) career advancement and financial reward; and (e) clear doctoral program expectations. These themes are consistent with previous research suggesting persistence and attrition in doctoral programs are associated with personal needs and institutional factors (Golde, 2006;Lovitts, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…To date, researchers have identified factors on both the student level and the institutional level that contribute to students' choice to leave doctoral programs (Golde, 2006;Lovitts, 2001). Research supports the conclusion that persistence is the product of the interaction of multiple factors (Nettles & Millet, 2006;Wao, 2010).…”
Section: Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…One reoccurring theme in the research seemed to be the impact of doctoral students' significant relationships on their experiences. For example, couples in both asymmetrical marriages (one spouse enrolled in a doctoral program) and symmetrical marriages (both partners enrolled in a doctoral program) reported having difficulty adjusting to and coping with the all-consuming graduate lifestyle (Gold, 2006;Scheinkman, 1988). In contrast, Cymbal (2004) reported that doctoral students felt more satisfied in their marriages, had more time to spend with their spouses, and had increased affective communication while pursuing a doctoral degree.…”
Section:   mentioning
confidence: 99%
“…Extant literature on graduate student relationships focuses on the graduate students' perspective. Specifically, previous research examines how graduate training affects marital dynamics (Feldman, 1973;McRoy & Fisher, 1982;Brannock et al, 2000;Gold, 2006;Price, 2006). In this paper, we take a different approach.…”
Section: Introductionmentioning
confidence: 99%